2008
DOI: 10.1002/jcp.21665
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear matrix binding site in the Rad51 recombinase

Abstract: It has been shown that the key homologous recombination protein Rad51 accumulates in DNA damage-induced nuclear foci that are attached to the nuclear matrix. In the present communication we attempted to find whether Rad51 contains a functional domain responsible for nuclear matrix binding. By alignments of the sequences encoding nuclear matrix targeting signals of human nuclear matrix binding proteins with the whole length human Rad51sequence a putative nuclear matrix targeting signal was identified. To prove … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This region is important for binding of RAD51 to the nuclear matrix (Nagai et al, 2008;Mladenov et al, 2009). The nuclear matrix is a dynamic subnuclear compartment supporting the spatial organization of DNA metabolism (Anachkova et al, 2005;Zaidi et al, 2007;Courbet et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This region is important for binding of RAD51 to the nuclear matrix (Nagai et al, 2008;Mladenov et al, 2009). The nuclear matrix is a dynamic subnuclear compartment supporting the spatial organization of DNA metabolism (Anachkova et al, 2005;Zaidi et al, 2007;Courbet et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that SIM is required for the accumulation of RAD51 at DNA damage. Although RAD51 is localized to both the nucleus and cytoplasm (Mladenov et al, 2009), the EGFP-tagged RAD51-AAAS and RAD51-V264K proteins showed cytoplasmic-dominant distributions, compared with RAD51-WT in GM0637 cells (supplementary material Fig. S4A).…”
Section: Rad51 Interacts With Sumo Through Its Sim Domainmentioning
confidence: 99%